Respuesta :
2/3(x - 2) = 4x
The first thing to do is use the distributive property to get rid of the parentheses.
2/3 • x = 2/3x
-2 • 2/3 = -1.33...
This leaves us with 2/3x - 1.33 = 4x
Next, you must isolate the variable to be on only one side.
Do this by subtracting 2/3x from both sides.
2/3x - 2/3x = 0
4x - 2/3x = 3.33x
This makes the new equation -1.33 = 3.33x
Next, just divide both sides by 3.33.
3.33x / 3.33 = x
-1.33 / 3.33 = -0.399399...
This means x = -0.399399....
Or you can round this to x = -0.4
The first thing to do is use the distributive property to get rid of the parentheses.
2/3 • x = 2/3x
-2 • 2/3 = -1.33...
This leaves us with 2/3x - 1.33 = 4x
Next, you must isolate the variable to be on only one side.
Do this by subtracting 2/3x from both sides.
2/3x - 2/3x = 0
4x - 2/3x = 3.33x
This makes the new equation -1.33 = 3.33x
Next, just divide both sides by 3.33.
3.33x / 3.33 = x
-1.33 / 3.33 = -0.399399...
This means x = -0.399399....
Or you can round this to x = -0.4